A peculiar case of a runaway ambassador: Yi Sang-Cho's defection and the 1956 crisis in North Korea. Issue 2 (3rd April 2019) - Lankov, Andrei; Selivanov, Igor
ABSTRACT: The defection of Yi Sang-cho, the North Korean ambassador to Moscow, in 1956 was an event without precedent in the history of the communist bloc. This article deals with the background to the event, drawing on newly available archival documents and other sources. The study indicates that Ambassador Yi, deeply involved with intra-party opposition in North Korea, played a major role in the Mikoyan-Peng delegation's trip to Pyongyang and subsequent events. It also traces why the Soviet authorities decided to grant asylum to Yi Sang-cho, and how Moscow's attitude to his defection changed over time.